Confinement of non-neutral proton plasma within a bent magnetic mirror field: 3D PIC simulation - Xiao-Jing Zhang; Yong Sun; Liang-Wen Chen; Fang-Ping Wang; Wen-Shan Duan (AIP Advances, 2023)
We conducted a study on the confinement properties of non-neutral proton plasma in an asymmetric magnetic mirror using the three-dimensional (3D) particle-in-cell simulation method. Our findings indicate a close relationship between the ability of the magnetic mirror to confine protons and the incidence orientation of the proton beam. This relationship can only be accurately assessed through 3D simulation, as opposed to two-dimensional simulation. In addition, we observed that a higher velocity parallel to the magnetic field direction results in a shorter confinement time. The electric field at and near the central point of the mirror exhibits quasi-periodic vibrations, attributed to the electrostatic oscillation of the proton and the cyclotron motion. Furthermore, we discovered a drift motion of the confined proton plasma in the direction of the magnetic field gradient. These findings hold implications for the design of magnetic mirrors capable of effectively confining charged particle beams.